Agri-environmental assessment of the agrochemical containers and solid waste in Calimaya, central Mexico - Amorim Homem de Abreu Loureiro, Guilherme; Escalona Valdez, Rodrigo Antonio; Juan Pérez, José Isabel; Balderas Plata, Miguel Ángel; Amaya Chávez, Araceli; Sánchez Meza, Juan Carlos (Revista de Ciências Agro-Ambientais, 2024)
The management of agrochemical containers and solid waste is a potential indicator of environmental sustainability of the cropland use, due to it is associated with the crop technological level, the management practices of farmers and the public and private initiatives of society. The objective of this research was to identify, characterize and analyse the diversity of agrochemical containers and the final disposal of solid waste in the agricultural and forest cropping areas in the Municipality of Calimaya, State of Mexico. It was analysed 119 cropping areas out in the rural zone in the period between August to November 2019. Evidence of incorrect handling of solid residues and the disposal of agrochemical packaging, mainly pesticides and fertilizers, was found, highlighting the practices of discarding solid residues in cropping areas, predominantly maize (Zea mays L.) and potato (Solanum tuberosum L.) crops, as well as the burning of these wastes or their abandonment in water bodies.